Enhancing a Better Job Performance through Work-Life Balance: Mediating-Moderating Effect of Employee Engagement and Affective Commitment - Miftahudin, Adi; Maulidiah, Syifa; Muhamad Alwi (Universitas Negeri Semarang, 2025)
The Indonesian shipbuilding industry, contributing approximately 4% to the national GDP, faces significant operational challenges, impacting its projected growth targets for 2025. This study investigates the mediating roles of employee engagement and the moderating role of affective commitment in linking work-life balance to job performance. Using a quantitative-explanatory approach, a survey was conducted with 173 employees of PT. Kodja Bahari, analyzing data via Structural Equation Modeling - Partial Least Squares (SEM-PLS). The research at PT. Kodja Bahari found that work-life balance (WLB) significantly impacts job performance (JP), with employee engagement (EE) acting as a mediator between them. Affective commitment (AC) also plays a role, strengthening the relationship between WLB, EE, and JP. To improve job performance, PT. Kodja Bahari should adopt more flexible work policies, such as adjustable working hours and remote work options. The company should invest in training programs to enhance employees' skills and foster stronger emotional attachment to the company through recognition and rewards. However, the study's results are limited to one company, so future research should involve multiple companies and additional statistical methods for more comprehensive, as well as applying a longitudinal design.